2020
DOI: 10.1038/s41598-020-69904-0
|View full text |Cite
|
Sign up to set email alerts
|

Radial shock waves prevent growth retardation caused by the clinically used drug vismodegib in ex vivo cultured bones

Abstract: In childhood medulloblastoma patients, the hedgehog antagonist vismodegib is an effective anticancer treatment but unfortunately induces irreversible growth arrests and growth impairment limiting its use in skeletally immature patients. We hypothesized that radial shock wave treatment (rSWT) may protect drug-induced growth impairment owing to its osteogenic effects. Fetal rat metatarsal bones were exposed to vismodegib (day 0-5; 100 nM) and/or rSWT (single session); other bones from day 1 were continuously exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Of note, we observed that co-treatment with HNG not only prevented venetoclax-induced growth impairment but also restored the histomorphology and the organization of the growth plate chondrocytes. Interestingly, in a similar organ culture system we earlier reported that shockwave treatment can prevent growth retardation and growth plate disorganization caused by vismodegib, an Indian hedgehog inhibitor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we observed that co-treatment with HNG not only prevented venetoclax-induced growth impairment but also restored the histomorphology and the organization of the growth plate chondrocytes. Interestingly, in a similar organ culture system we earlier reported that shockwave treatment can prevent growth retardation and growth plate disorganization caused by vismodegib, an Indian hedgehog inhibitor [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The height of the resting + proliferative (R + P) zone was measured at 10 different regions of the metatarsal growth plate, and the size of hypertrophic cells was averaged based on measurements from 10 different hypertrophic cells at the proximal and distal ends. A cell was considered hypertrophic if the longitudinal height was bigger than 7 μm, as previously described [ 29 ]. Analyses were performed in a blinded manner with Image J software (National Institutes of Health).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the clinical application of vismodegib regulating the Ihh signaling pathway needs to be particularly cautious, especially for juvenile patients with benign diseases. For example, the systematic application of vismodegib was reported to induce early epiphyseal closure in juveniles with cancers, which has received increasing attention [ [46] , [47] , [48] ]. To the best of our knowledge, the present study is the first to observe vismodegib causing early fusion of the metaphyseal in the vertebral body, and we further elucidate the possible mechanism that vismodegib causes IDD-like changes, at least in part, via inhibiting proliferation of IVDs chondrocytes and promoting apoptosis to disrupt cartilage homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). After dissection, each bone was transferred to a 24-well plate and cultured in minimum essential medium α (MEM-α, Invitrogen, Scotland) supplemented with 0.2% endotoxin-free BSA, 1 mM β-glycerophosphate, 0.05 mg/ml ascorbic acid and 20 μg/ml gentamycin at 37 °C under a humidified atmosphere with 5% CO 2 [ 10 ]. The medium was changed every 2 to 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of mechanical loading on ex vivo cultured bones have been investigated in numerous studies [ 8 ]. Ex vivo cultured fetal metatarsal bones are a well-established model for studying longitudinal bone growth and responsiveness to different growth-regulating factors, including insulin-like growth factor-I (IGF-1), glucocorticoids and radial shock waves [ 9 , 10 ]. Additionally, the fetal femur bone has a high density of growth plate chondrocytes, as visualized by histological staining, thus providing great potential for ex vivo studies of longitudinal bone growth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%